2014
DOI: 10.1128/aem.03452-13
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose as a Substrate for Microbial Cell Culture

Abstract: Bacterial cellulose (BC) has a range of structural and physicochemical properties that make it a particularly useful material for the culture of bacteria. We studied the growth of 14 genera of bacteria on BC substrates produced by Acetobacter xylinum and compared the results to growth on the commercially available biopolymers agar, gellan, and xanthan. We demonstrate that BC produces rates of bacterial cell growth that typically exceed those on the commercial biopolymers and yields cultures with higher titers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…We found that the PaQa reporter was induced upon growth on all hydrogels tested compared with induction in liquid, including agarose, gellan, alginate, and polyvinylalcohol-polyvinylpyrrolidone (PVA-PVP) hydrogels (Fig. 1B) (14,15). We conclude that PaQa expression is stimulated by physical properties of surfaces rather than their chemistry, because these hydrogels harbor distinct chemical moieties.…”
Section: Resultsmentioning
confidence: 77%
“…We found that the PaQa reporter was induced upon growth on all hydrogels tested compared with induction in liquid, including agarose, gellan, alginate, and polyvinylalcohol-polyvinylpyrrolidone (PVA-PVP) hydrogels (Fig. 1B) (14,15). We conclude that PaQa expression is stimulated by physical properties of surfaces rather than their chemistry, because these hydrogels harbor distinct chemical moieties.…”
Section: Resultsmentioning
confidence: 77%
“…[94][95][96] Alternatives for sheep blood, horse blood, and rabbit plasma should be explored; for example, goat, pig, and hair sheep (a breed of sheep adapted to tropical climates) blood are alternatives to sheep blood for homemade culture media, 97,98 but lyophilised or synthetic media should also be considered. Likewise, agar (ie, solidifying substrate in culture media) is obtained from sea algae at a few harvesting sites; substrates such as cellulose produced by engineered bacteria 99 should be assessed as a commercial alternative.…”
Section: Availability Of Equipment and Consumables Adapted For Use Inmentioning
confidence: 99%
“… 10 ), K. nataicola RZS01 11 , and Gluconobacter oxydans DSM 3504 were sequenced completely. Gluconacetobacter xylinus (formerly Acetobacter xylinum ) is one of the most commonly studied species because of its ability to produce relatively large amounts of BC from a wide range of carbon and nitrogen sources in liquid culture 3 , 4 , 12 and has become the most popular strain so far for manufacturing of various materials, including paper 13 , food packaging 14 , medical materials 15 , and cell culture 16 . It is difficult to obtain high productivity by means of G. xylinus in a large-scale fermentation system owing to its low yield under agitated culture.…”
Section: Introductionmentioning
confidence: 99%